Проблема домашнього насильства в Україні: на чиїй стороні соціум? - Возняк, Ярина (Видавництво Національного університету "Львівська політехніка", 2009)
In this article are researched the characteristic features of domestic violence in Ukraine. The author emphasizes on tight connection of Slavonic mentality and the behavior of women-victims being offended at home both with eyewitnesses of that crime. As a conclusion is offered the implementation of special subjects at schools and higher educational establishments.
Keywords: aggression; domestic violence; the vicious circle of violence; offence and brutal treatment to woman; gender education.